Design of a rhombus-type stick-slip actuator with two driving modes for micropositioning. (1st March 2022) - Shi, Beichao; Wang, Fujun; Huo, Zhichen; Tian, Yanling; Zhao, Xiaolu; Zhang, Dawei
Highlights: A novel rhombus-type displacement amplification mechanism is proposed. A novel stick–slip actuator with symmetric structure is developed. The motion speed and step displacement of forward/backward motion are consistent. A new driving method in which two driving feet act together is proposed. Abstract: This paper proposes a novel liner stick–slip actuator with compact structure which can achieve forward and backward motion. A novel rhombus-type displacement amplification mechanism (RTDAM) with symmetric structure is used to generate lateral motion to improve the actuator performance. Theoretical analysis and finite element analysis (FEA) are carried out to calculate the coupling ratio and natural frequency of the system. In addition, a new driving method in which two driving feet act together is proposed, which can improve the load capacity of the actuator. A prototype is fabricated and experimental tests are conducted to investigate its performance. The results indicate that the maximum speed of forward and backward motion are 428.5 μm/s and 443.2 μm/s, respectively. Compared with the single foot driving method, the load capacity of the actuator is increased from 1.2 N to 1.6 N by adopting the new driving method. Finally, a micropositioning stage is built utilizing the proposed stick–slip actuator and the experimental results indicate that the stage can work stably.